Ambient CFCs and HCFC‐22 observed concurrently at 84 sites in the Pearl River Delta region during the 2008–2009 grid studies. Issue 12 (19th June 2014) - Zhang, Yanli; Wang, Xinming; Simpson, Isobel J.; Barletta, Barbara; Blake, Donald R.; Meinardi, Simone; Louie, Peter K. K.; Zhao, Xiuying; Shao, Min; Zhong, Liuju; Wang, Boguang; Wu, Dui
Abstract Air samples were collected concurrently at 05:00 A.M. and 10:00 A.M. local Beijing time (geomagnetic time + 8) at 84 sites during two grid‐study campaigns on 29 September 2008 and 1 March 2009 in the Pearl River Delta region, in order to offer snapshots of ambient CFCs and hydrochlorofluorocarbons (HCFCs) in different seasons and to indicate the presence of local emission sources. Compared to the subtropical northern hemisphere background levels, mean mixing ratios of CFC‐11, CFC‐12, CFC‐113, CFC‐114, and HCFC‐22 were enhanced by 7%–11%, 8%–11%, 5%–6%, 8%–9%, and 71%–135%, respectively. When data from this tudy were pooled together with previous observations in the region, ambient CFC‐11, CFC‐12, and CFC‐113 unambiguously showed declines in mixing ratios, while HCFC‐22 showed an increase. Spatial variations revealed potential emission hot spots in the region, and levels of CFCs and HCFC‐22 were higher in September than in March due to many more refrigeration and air‐conditioning activities during summer. Source apportioning by positive matrix factorization revealed that new input of CFCs and HCFC‐22 into the ambient air was largely attributed to emission from air‐conditioning and refrigerating activities instead of industry activities. Average emissions in the region estimated by the CO‐tracer method were 0.8 ± 0.2, 1.4 ± 0.6, 0.2 ± 0.1, 0.1 ± 0.02, and 4.4 ± 1.0 Gg/yr for CFC‐11, CFC‐12, CFC‐113, CFC‐114, and HCFC‐22, respectively, and they accounted for 5.5%–25.5% of the total estimated CFC and HCFC‐22 emissions in China.